The Influence of Fashion Trends on Purchasing Decisions at Rani Collection Boutiques in Makassar - M, Fedrian; Baharuddin, Aris; Rivai, Andi Muhammad (Universitas Negeri Makassar, 2025)
This study aims to determine how much influence Fashion Trend has on Purchasing Decisions at Rani Collection Boutiques in Makassar. This research is a quantitative research with a total of 97 respondents using a descriptive approach. Data collection was carried out using observation techniques, questionnaires and documentation. The population in this study was 3,734 people. The sampling method used was using the Slovin formula, which was narrowed by 97 people. The data obtained from the research results were processed using the SPSS application with data analysis techniques used, namely validity and reliability tests, normality tests, simple regression analysis and the coefficient of determination. Based on the results of the study, it shows that: (1) The influence of fashion trends is in the very high category with a total percentage of 87.60%. (2) The Purchase Decision Level is also in the very high category with a percentage of 89.45%. (3). The Influence of Fashion Trends on Purchasing Decisions at Rani Collecion Boutiques in Makassar is in the strong category with a percentage of 0.728 or 72.8%.